3D Printing of Flexible Liquid Sensor Based on Swelling Behavior of Hydrogel with Carbon Nanotubes. Issue 2 (27th November 2018) - Li, Xiangjia; Yang, Yang; Xie, Benshuai; Chu, Ming; Sun, Haofan; Hao, Siyang; Chen, Yiyu; Chen, Yong
Abstract: Flexible sensors with accurate detection of environmental stimuli (e.g., humidity and chemical substances) have drawn increasing research interests in biomedical engineering and environmental science. However, most work is focused on isotropic sensing of liquid occurrence due to the limitation of material development, sensor design, and fabrication capability. 3D printing is used to build multifunctional flexible liquid sensors with multimaterials enabling anisotropic detection of microliquid droplets, and described herein. Electrical conductive composite hydrogels capable of detecting chemical liquid are developed with poly (ethylene diacrylate) (PEGDA) and multiwalled carbon nanotube (MWCNT). Due to the absorption of the liquid droplet and related swelling behavior, the resistance of PEGDA/MWCNT composite hydrogel increases dramatically, while the resistance of pure PEGDA hydrogel decreases significantly. Based on the two composite hydrogels and the related 3D printing method, a mesh‐shaped liquid sensor that can effectively identify the position and volume of liquid leakage in a short time is developed. Furthermore, a three‐layered liquid sensor to enable bidirectional monitor and detection of the liquid leakage in two different sides is demonstrated. The 3D‐printed liquid sensor offers a distinctive perspective on the potential applications in various fields for detection of liquid leakage in accurate position and direction. Abstract : A 3D‐printed liquid sensor with the capability of detecting the position and direction of liquid leakage is developed. The liquid sensor for microdroplet, made with conductive fillers and hydrophilic hydrogel, shows high sensitivity and quick response. It opens intriguing perspectives for designing 3D‐printed sensors with special distribution of composite hydrogels to achieve anisotropic sensing characteristics.